Natural conditions as a premise for the development of the Poznań urbanised area - Mizgajski, Andrzej; Bródka, Sylwia; Fagiewicz, Katarzyna; Kijowska, Jolanta; Łowicki, Damian; Markuszewska, Iwona; Poniży, Lidia (My University, 2010)
This paper presents the natural conditions in the Poznań urbanised area with a focus on lasting preservation of the resources both in respect of quantity and quality. The problem related sections concern the land surface, mineral resources, soil, water and assets of natural systems. The content shows elements of a nature potential diagnosis considering the forms of human pressure and condition of the environment’s components. Based on the above conclusions were drawn regarding the actions necessary to preserve or improve the nature-related aspects of the population’s quality of life. The purposefulness and scope of the current and planned co-operation between communes as regards environment management were assessed.
Keywords: Poznań; urbanised area; natural conditions; urbanisation